Diversity in the organization of elastin bundles and intramembranous muscles in bat wings - Cheney, Jorn A. (J Anat, 2017)
Unlike birds and insects, bats fly with wings composed of thin skin that envelops the bones of the forelimb and spans the area between the limbs, digits, and sometimes the tail. This skin is complex and unusual; it is thinner than typical mammalian skin and contains organized bundles of elastin and embedded skeletal muscles. These elements are likely responsible for controlling the shape of the wing during flight and contributing to the aerodynamic capabilities of bats. We examined the arrangement of two macroscopic architectural elements in bat wings, elastin bundles and wing membrane muscles, to assess the diversity in bat wing skin morphology. We characterized the plagiopatagium and dactylopatagium of 130 species from 17 families of bats using cross‐polarized light imaging. This method revealed structures with distinctive relative birefringence, heterogeneity of birefringence, variation in size, and degree of branching. We used previously published anatomical studies and tissue histology to identify birefringent structures, and we analyzed their architecture across taxa. Elastin bundles, muscles, neurovasculature, and collagenous fibers are present in all species. Elastin bundles are oriented in a predominantly spanwise or proximodistal direction, and there are five characteristic muscle arrays that occur within the plagiopatagium, far more muscle than typically recognized. These results inform recent functional studies of wing membrane architecture, support the functional hypothesis that elastin bundles aid wing folding and unfolding, and further suggest that all bats may use these architectural elements for flight. All species also possess numerous muscles within the wing membrane, but the architecture of muscle arrays within the plagiopatagium varies among families. To facilitate present and future discussion of these muscle arrays, we refine wing membrane muscle nomenclature in a manner that reflects this morphological diversity. The architecture of the constituents of the skin of the wing likely plays a key role in shaping wings during flight.